REPRESENTASI MISKONSEPSI PESERTA DIDIK PADA MATERI SUHU DAN KALOR - Edy Purwanto; Winarti Winarti (Papua Journal of Physics Education, 2020)
Physics learning is not just about working on mathematical equations. It is more important to understand the concepts. The initial conception owned will greatly affect misconceptions. This study aimed to determine the description of misconceptions on the temperature and heat concepts of students at MAN 4 Bantul, Yogyakarta. This research used quantitative descriptive. This study was done using two techniques, namely test and non-test techniques. Test technique was done using three tier type diagnostic questions instrument. This research was conducted at MAN 4 Bantul Yogyakarta with a total sample of 38 students who had participated in the learning of temperature and heat material. The diagnostic instruments used for this study were contained of 20 questions. Before the questions were used, the test validity and reliability were first analyzed. Analysis of the data was done to categorize the category of students' conceptual understanding on the material of temperature and heat. Students' answers from each item of diagnostic tests were categorized into several categories of answers. The results of this study indicated that there were 5.26% of students who understood the concept, 55.26% of students experienced misconceptions, 31.59% of students held a lack of knowledge, and 7.89% of students were picking error answers. There were several obtained findings that became students' misconceptions of the material temperature and heat, including the concept of temperature and the concept of expansion.Keywords: Misconception, temperature and heat concepts.